Potentially Preventable Deaths by Intensive Care Medicine in Mongolian Hospitals - Naranpurev Mendsaikhan; Tsolmon Begzjav; Ganbold Lundeg; Martin W. Dünser (Critical Care Research and Practice)
Purpose. To evaluate the portion of hospitalized patients dying without prior intensive care unit (ICU) admission and assess whether death could have been prevented by intensive care. Methods. In this prospective, observational, multicenter study, data of adults dying in and outside the ICU in 5 tertiary and 14 secondary hospitals were collected during six months. A group of experts categorized patients dying without prior ICU admission as whether their death was potentially preventable or not. Results. 617 patients died (72.9% in and 27.1% outside the ICU) during the observation period. In 54/113 patients (32.3%) dying in the hospital without prior ICU admission, death was considered potentially preventable. The highest number of these deaths was seen in patients aged 16–30 years and those who suffered from an infection (83.3%), underwent surgery (58.3%), or sustained trauma (52%). Potentially preventable deaths resulted in a total number of 1,078 years of life lost and 709 productive years of life lost. Conclusions. Twenty-seven percent of adults dying in Mongolian secondary and tertiary level hospitals do so without prior ICU admission. One-third, mostly young patients suffering from acute reversible conditions, may have potentially been saved by intensive care medicine.